P839 Clinical activity in inflammatory bowel diseases is associated with consumption of processed foods. (30th January 2023) - Sarbagili Shabat, C; Zelber-Sagi, S; Fliss Isakov, N; Hirsch, A; Ron, Y; Thurm, T; Maharshak, N
Abstract: Background: Western diet and its food components have been suggested to influence inflammatory bowel diseases (IBD) clinical course. However, the association of dietary processing factors and disease activity is uncertain. We aimed to evaluate whether intake of foods with varying processing levels is associated with disease activity in IBD patients. Methods: A cross-sectional study of adult patients with IBD was performed at a tertiary center between August 2019 to June 2022, by collecting clinical and dietary data from consecutive patients who signed an informed consent form. Clinical activity was defined using HBI (Crohn's disease) and SCCAI (ulcerative colitis). Dietary intake was assessed using a dedicated validated processed food questionnaire (PFQ) that categorizes dietary intake into three groups of processed food levels: unprocessed or minimally processed, processed, and ultra-processed. Adjusted odds ratios for disease activity were determined using a multivariate logistic regression. Results: A total of 242 IBD patients (62.8% Crohn's disease patients) were enrolled, of whom 73.1% were in clinical remission. Comparing the higher tertile to the lowest tertile of foods consumption - unprocessed foods (OR 0.29, 95% CI 0.13-0.65) and processed foods (OR 0.40, 95% CI 0.19-0.82) were negatively associated with disease activity, while high consumption of ultra-processed foods was positively associated with active disease (OR 2.24, 95% CI 1.05-4.77). All ultra-processed food subgroups were positively associated with higher odds of active disease. Conclusion: Higher intake of unprocessed or minimally processed foods was associated with lower odds of clinically active IBD, while higher ultra-processed foods intake was associated with higher odds of active disease. Further studies are needed to evaluate the impact of different levels of food processing on disease activity.